The Sharing Economy in China's Aging Industry: Applications, Challenges, and Recommendations - Yaolin Hu; Jian Wang; Stephen Nicholas; Elizabeth Maitland (JMIR Publications, 2021)
BackgroundAll aging societies face the challenge of allocating limited resources for the highest value of use. The sharing economy provides one method to address the imbalance between the demand and supply of health services to the older adult population. With a substantial aging population, China's practices in the sharing aging industry may set examples for other "getting old before getting rich" countries. ObjectiveThere is a gap in both the data and research on China's aging industry sharing economy. This paper addresses these data and research lacunae by constructing a framework for the application of a sharing model in China's aging industry, by assessing the current state of the aging industry sharing economy, by setting out the challenges to the sharing aging health care and service economy, and by making recommendations for the development of the aging industry sharing economy. MethodsThis paper constructs a sharing economy framework in the aging industry covering four aspects (people, facilities, capital, and information) to test the current state and future prospects of China's aging industry sharing economy. ResultsIn people sharing, we analyzed the sharing of emotional companionship, doctors, nurses, nursing attendants, and domestic helpers. We discussed facility sharing models from the point of land and housing, medical devices, and other items such as pensioner meals and shared medicine bins. We acknowledge that crowdfunding platforms have developed fast in China, but many older adult users faced problems in their operation. Information sharing is a developing field, which can optimize users' experiences and should help older adults filter out misinformation, but China currently does not have adequate sharing information platforms for older adults. ConclusionsWe identified four major challenges in China's aging industry sharing economy: poor adaptability to technology for older adults, mediocre quality of shared services, one-size-fits-all and the concept of the useless elderly, and shortage of qualified practitioners. We make recommendations for specific measures by governments, communities, and enterprises to improve the sharing economy in the aging industry.